Household and Contextual Factors Influencing Payment of Education by Households in Ghana - Abbam, Anthony (European Scientific Journal, ESJ, 2018)
Using data from the sixth round of the Ghana Household Living Standards Survey, this paper examines issues relating to household educational expenditure with a view to deriving implications for policy direction. The key findings from the estimated Tobit model in this paper are as follows: First, household income has significant positive influence on household expenditure on education. Thus, increase in household income is associated with an increase in educational expenditure. Second, there was a negative significant relationship between household poverty and demand for education. Third, female headed household is a positive significant determinant of expenditure on education. Finally, contextual factors such as locality are very crucial in determining household educational expenditures. The paper recommends for equality of educational opportunity so that children from economically handicapped families and less endowed communities have the same playing field as their well-to-do counterparts. Further, policy strategies to improve income generating activities of households should be pursued and the design of schemes specifically to offer assistance for those who are economically vulnerable.